Freelance your way to freedom : how to free yourself from the corporate world and build the life of your dreams - Fasulo, Alexandra (John Wiley & Sons, Inc., 2023)
"Freelance Your Way to Freedom is the gig economy Bible that every person needs to start a side hustle with serious profitable potential today. This book will provide actionable advice, real-world scenarios, and personal tips that have enabled Alex to take her freelancing profile from $36,000/year in 2015, to a 7-figure empire in 2021. With unique insights that come from an individual who had virtually no preparation for working on her own, navigating the gig economy, or managing money, Freelance Your Way to Freedom covers those critical moments in business when decisions need to be made quickly and without warning. By leveraging Alex's personal story, filled with relatable struggles, mindset challenges, difficulties in business as a woman, this book is packed with relatable anecdotes, practical tips, and hands-on examples that will help readers put down the book, open their laptop, and make the gig economy work for them. As a digital nomad, social media influencer, and photographer herself, Alex will include photos from her perspective as a gig economy worker throughout the journey. Freelance Your Way to Freedom will unapologetically break down both the good and the bad of this new, decentralized market- place that just can?t seem to be tamed. But to people like Alex, the wildness of the gig economy is what makes the adventure that much more fun"--